2011
DOI: 10.1142/s0218127411028465
|View full text |Cite
|
Sign up to set email alerts
|

Controller Design and Analysis for a Two-Cell Dc-Dc Converter in the Presence of Saturation

Abstract: In this work, a zero static error proportional controller for a two-cell DC-DC buck converter is synthesized and analyzed. Under a traditional proportional control scheme, the system presents a constant error of the current supplying the output load. As the proportional feedback gain is increased, the average static error decreases. However, subharmonic oscillations and chaotic behavior emerge beyond successive bifurcations. To achieve zero current and zero voltage static error, we suggest a modification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For the sake of reducing the number of parameters of the system, the following dimensionless and simplified model can be considered [27]:…”
Section: Two-cell Dc-dc Convertermentioning
confidence: 99%
See 1 more Smart Citation
“…For the sake of reducing the number of parameters of the system, the following dimensionless and simplified model can be considered [27]:…”
Section: Two-cell Dc-dc Convertermentioning
confidence: 99%
“…Equation ( 35) can be simplified after substituting Δσ i (k) ≡ σ i (k + 1) − σ i (k) and equation (27) at k + 1 time steps:…”
Section: Proofmentioning
confidence: 99%
“…To overcome these limitations, some improvements of the linear techniques have been suggested. In [17], the linear controller has been improved using Lyapunov theory to control the two-cell DC-DC buck converter and obtain a global fast response with zero steady-state error in the presence of the duty cycle saturation. The time-delayed feedback controller is another method that has been widely used in conjunction with the proportional controller in order to improve the DC-DC converter behavior [18][19][20] as well as the H-bridge inverter [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In [Robert & El Aroudi, 2006], authors have shown that the proportional controller based PWM control signal leads to chaotic behavior in the multicell converter when the gain is raised beyond a critical value. To improve its performance, some new controller schemes have been proposed to control the two-cell buck converter Hamza et al, 2011;Kaoubaâ et al, 2012]. Nevertheless, a chaotic behavior still exists outside a stability region.…”
Section: Introductionmentioning
confidence: 99%